Ratification of the Biodiversity Beyond National Jurisdiction Agreement: Implications for Indonesia’s National Interests and Implementation Challenges - Indrawati, Nanda; Setyardi, Untung (Fakultas Hukum Universitas Pattimura, 2026)
Introduction: Areas Beyond National Jurisdiction (ABNJ) cover approximately two-thirds of the world's oceans. These areas play a vital role in maintaining the balance of the global marine ecosystem. However, the United Nations Convention on the Law of the Sea 1982 does not comprehensively regulate the conservation and utilisation of marine biodiversity in these areas. This legal vacuum led to the creation of the Agreement on Marine Biological Diversity of Areas Beyond National Jurisdiction (BBNJ Agreement). Indonesia has ratified this agreement through Presidential Regulation No. 67 of 2025, which has legal implications for the national legal system.Purposes of the Research: This article aims to analyse the implications of ratifying the BBNJ Agreement for Indonesia's national interests and the challenges of implementing it within the national legal system.Methods of the Research: This study uses a normative legal research method with a legislative and conceptual approach through a review of relevant international legal instruments and national legislation.Results of the Research: The results of the study show that ratification of the BBNJ Agreement is strategically crucial for Indonesia as an archipelagic and developing country, particularly through the four main pillars of the BBNJ Agreement, namely the regulation of marine genetic resources and benefit sharing, area-based management tools, environmental impact analysis, and capacity building and marine technology transfer. However, ratification also poses legal and institutional challenges, including the need to harmonize national legislation, regulate marine genetic resources and digital sequence information, strengthen inter-ministerial coordination, and adjust law enforcement mechanisms for Indonesian citizens' activities in international waters. Therefore, follow-up measures are needed to strengthen the national legal and institutional framework so that the implementation of the BBNJ Agreement can proceed effectively and in line with Indonesia's national interests.